Impact of Mangrove Land Use on the Carbon Stock in an Abandoned Shrimp Pond: A Case Study at Samut Songkhram Campus, Suan Sunandha Rajabhat University, Thailand - Wongprom, Jetsada; Inthiraj, Anantachai; Songsin, Niwat; Somporn, Kanokporn; Pianjing, Prisna (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Changes in land use within coastal areas have significantly impacted the carbon stock of mangrove forests. This study examined three different land-use types including the abandonment of shrimp ponds characterized as restored mangrove forests (RMF), logged Avicennia marina (LAM) stands, and abandoned shrimp ponds (ASP) on the carbon stock in plant and soil. Eight experimental plots, each measuring 20 m x 20 m, were established in the RMF and LAM to assess the forest structure. The diameter and height of mangrove trees were measured, and both the above and belowground biomass were estimated. Three soil samples were collected randomly from each site at four different depths (0–15 cm, 15–30 cm, 30–50 cm, and 50–100 cm) to analyze the soil characteristics. Bulk density and carbon concentration were then determined from these samples. The Tukey test estimated and statistically analyzed vegetation, soil, and carbon stocks. The results indicate that the forest structure and biodiversity in RMF were higher than in LAM. Additionally, vegetation biomass and carbon stock in RMF exceeded the values estimated for LAM. The soil carbon stock at 0–100 cm depths across RMF, LAM, and ASP was similar, ranging from 204.52 to 220.20 t.C.ha-1. Nonetheless, the largest ecosystem carbon stock was estimated for RMF (306.52 t.C.ha-1), demonstrating the influence of land-use patterns on ecosystem carbon storage. According to the results, it might take longer for the ecosystem carbon in the abandoned shrimp pond in ASP to recover than it would in RMF and LAM. However, mangrove restoration in abandoned shrimp ponds is crucial to improve the forest structure, encourage ecological advantages, and accelerate carbon stock recovery. Keywords: abandoned shrimp pond, carbon stock, land use, mangrove forest, Samut Songkhram campus